1999
DOI: 10.1093/qjmed/92.12.707
|View full text |Cite
|
Sign up to set email alerts
|

Capture-recapture-adjusted prevalence rates of type 2 diabetes are related to social deprivation

Abstract: We examined the prevalence of type 2 diabetes and social deprivation in one urban district in Liverpool from October 1995 to September 1996 inclusive. This area has a stable Caucasian population of 176, 682. Lists were made of all known diabetics attending six different medical points of contact during the year, and were condensed and aggregated to eliminate duplicates. From postcode data, each patient was assigned to residence in one of the 14 electoral wards in the district, for which demographic structure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
27
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 10 publications
5
27
1
Order By: Relevance
“…In understanding disease risk, it is critical to acknowledge broad factors underpinning inequitable distributions of disease such that adverse health is concentrated among the more disadvantaged [7,8]. Diabetes is more common among the poor and excluded [9,10], and diabetes risk factors have been shown to be most prevalent among the most socioeconomically disadvantaged [11][12][13][14][15][16][17]. Additionally, once diagnosed with diabetes, individuals of lower socioeconomic status (SES) are at greater risk of mortality compared to those of higher SES [10,18].…”
Section: Introductionmentioning
confidence: 99%
“…In understanding disease risk, it is critical to acknowledge broad factors underpinning inequitable distributions of disease such that adverse health is concentrated among the more disadvantaged [7,8]. Diabetes is more common among the poor and excluded [9,10], and diabetes risk factors have been shown to be most prevalent among the most socioeconomically disadvantaged [11][12][13][14][15][16][17]. Additionally, once diagnosed with diabetes, individuals of lower socioeconomic status (SES) are at greater risk of mortality compared to those of higher SES [10,18].…”
Section: Introductionmentioning
confidence: 99%
“…T2DM seems to be common in all populations in industrialized countries affecting disproportionately socially and materially disadvantaged adults [9][10][11][12][13][14]. The risk of diabetes is also greater for people who are obese [15], physically inactive [16], or have hypertension [17], all these conditions being more common among people with low socioeconomic position.…”
Section: Introductionmentioning
confidence: 99%
“…Low socioeconomic status (SES) is associated with type 2 diabetes mellitus in industrialized countries [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Prospective studies showed that elevated concentrations of acute-phase proteins like C-reactive protein (CRP) and cytokines are predictive of type 2 diabetes [16].…”
Section: Introductionmentioning
confidence: 99%